Effect of plant growth regulators in inducing Vitisvinifera Callus and increased production of flavonoids in vitro - shaker, Fatima kadhom; Mohammed , Sarab Abdul Hadi; Kadhim, Zaid Khaleel (Journal of Kerbala for Agricultural Sciences, 2024)
This study was aimed to use of plant tissue culture technology to induce callus from grapevine Vitisvinifera and stimulate it to increase the production of flavonoids. The study was carried out in two stages after the sterilization process was carried out: The first included establishing callus farms by cultivating cuttings containing a single node after completing their sterilization and cultivating them on MS medium containing 2,4-D and BA at different concentrations (0, 1, 2, 3,4) mg L -1and BA in concentrations (0, 0.1, 0.2, 0.4) in independent experiments. The second phase included studying the effect of growth regulators on the concentrations of carbohydrates and flavonoids in the callus induced from the first experiment. The results of the study showed the superiority of auxien 2,4-D at a concentration of 2mg L -1as it achieved the highest average fresh and dry weight of callus, reaching (3.32 and 1.03) mg respectively, while BA at a concentration of 0.2 mg L -1 achieved the highest average fresh and dry weight of callus was (1.91 and 0.51) mg respectively. The results also showed that the MS medium prepared with a concentration of 4 mg L -1of 2,4-D was significantly superior in the average concentration of the compounds Hesperdine, Nargnine, Proanthocyanin, and Rutin, reaching (64.94, 62.56, 55.63, and 71.22)% respectively.While the medium prepared with a concentration of 3 mg L -1outperformed 2,4-D achieved the highest concentration of Quercetin compounds reaching 75.36% compared to the neutral treatment, which achieved the lowest concentrations.